A systematic review of managerial competencies in global higher education - Connie, Connie; Kristiawan, Muhammad; Rusly, Muhammad; Hutami, Sari; Viona, Elsa (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to explore and synthesize essential managerial competencies required in higher education institutions amid globalization. Utilizing a systematic literature review methodology, this research examines peer-reviewed articles published within the last five years to identify key managerial skills that support institutional performance and adaptability. The review reveals that transformational leadership, strategic management, digital fluency, human resource effectiveness, and sustainability practices are among the most emphasized competencies. Findings indicate that institutional competitiveness is anchored in five foundational competencies: conceptual thinking, interpersonal communication, technical expertise, time management, and effective decision-making. The study concludes that higher education leaders must continually adapt by integrating emerging competencies such as data analytics, cross-cultural leadership, and crisis management. These skills are essential for navigating the dynamic demands of global education. The practical implication of this review lies in its potential to inform leadership development programs, institutional policies, and human capital strategies within higher education institutions. Future research is recommended to explore the dynamic interplay between traditional competencies and evolving global trends in educational leadership.